Explaining the Mental Health Consequences of Internalized Racial Oppression: The Mediating Roles of Family Resilience and Collective Action. - Ribas, Anna Luiza; Miranda, Mariana P.; Do Bú, Emerson Araújo (Journal of Marital & Family Therapy, 2025)
Racial oppression's institutional and interpersonal levels have had a substantial amount of empirical attention. Internalized racial oppression (IRO) and the paths through which it negatively impacts mental health have received considerably lesser attention. In this cross‐sectional study with 226 self‐identified Black participants, we focus on colonial mentality, as a form of IRO, and its association to depression. We argue that this detrimental effect happens because IRO limits the access to social identity resources, at both levels of the family system and wider society. The results revealed that the communication/problem‐solving dimension of family resilience mediated the effect of colonial mentality on depression. Support for the Black Lives Matter movement, a measure for collective action, was also a significant mediator but was, however, positively associated with depression. This study is the first to quantitatively assess IRO's consequences on the mental health of Black individuals in a postcolonial European country. We discuss clinical implications.